The Human Leukocyte Antigen-DPB1 Degree of Compatibility Is Determined by Its Expression Level and Mismatch Permissiveness: A German Multicenter Analysis - Mytilineos, Daphne; Tsamadou, Chrysanthi; Neuchel, Christine; Platzbecker, Uwe; Bunjes, Donald; Schub, Natalie; Wagner-Drouet, Eva; Wulf, Gerald; Kröger, Nicolaus; Murawski, Niels; Einsele, Hermann; Schaefer-Eckart, Kerstin; et al. (Frontiers in Immunology, 2021)
T cell epitope matching according to the TCE 3 algorithm classifies HLA DPB1 mismatches in permissive and non permissive. This classification has been shown to be predictive for mortality and acute GvHD (aGvHD) events in large international cohorts. We performed retrospective HLA DPB1 typing with an Illumina amplicon NGS based assay in 3523 transplant pairs with various hematological disorders transplanted in Germany between 2000 and 2014. Of these patients 2450 (69.5%) were 10/10 HLA matched and 1073 (30.5%) were 9/10 HLA matched. Stem cell source was PBSC in 3291 cases (93.4%) and bone marrow in the remaining cases. Myeloablative conditioning was performed in 2200 (62.4%) cases. Median patient age was 53 years. Non permissive HLA DPB1 mismatches were associated with a significantly higher risk of aGvHD and non relapse mortality (HR 1.36 and 1.21, respectively), which translated into worse GvHD and relapse free survival (HR 1.13). Effects on GvL and GvHD appeared strongest in non permissive mismatches with a GvH vector. We also extended the TCE3 matching with a hierarchical HLA DPB1 expression model including the rs9277534 polymorphism. In this model, non permissive HLA DPB1 mismatches showed significantly increased aGvHD risk if they were accompanied by two HLA DPB1 mismatches in GvH direction (HR: 1.46) or one mismatched highly expressed patient allotype (HR: 1.53). Our study confirms the predictiveness of the TCE3 matching algorithms. HLA DPB1 matching may further be refined by including additional HLA DPB1 mismatch parameters. In particular, DP non permissiveness associated with two HLA DPB1 mismatches or at least on highly expressed mismatched patient allotype should be avoided.